David Noy and Hanswulf Bloedhorn. Inscriptiones Judaicae Orientis. III Syria and Cyprus. Texts and Studies in Ancient Judaism 102. Tübingen: Mohr Siebeck, 2004. 284 pp. - Bowman, Steven B. (AJS review, 2005)
David Noy has labored in the past decade to update J. B. Frey's Corpus inscriptionum iudaicarum (vol. 1 [Rome 1936; revised by B. Lifshitz, New York, 1975]; vol. 2 [Rome, 1952]). He has already produced two volumes on the North Mediterranean (the Balkans and southern Italy, 1993, and Rome, 1995) and another for Greco-Roman Egypt (with William Horbury, 1992).